2020
DOI: 10.1039/d0ee00666a
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine vapor-assisted construction of heterostructured Ni2P/NiTe2 catalysts for efficient hydrogen evolution

Abstract: A PH3 vapor-assisted phase and structure engineering strategy to convert non-active NiTe into super-active Ni2P/NiTe2 catalysts for hydrogen evolution reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(62 citation statements)
references
References 39 publications
1
61
0
Order By: Relevance
“…Electrochemical nitrogen reduction reaction (NRR) powered by renewable energy sources is potentially a sustainable approach for nitrogen (N 2 ) fixation. However, the inert nature of N 2 and intensive competition from hydrogen evolution reaction (HER) impede its performance with sluggish kinetics and low selectivity [3–7] . Ru‐based transition metal catalysts are active catalysts for NRR at ambient conditions that can activate and polarize the inert N 2 molecule by accepting and donating electronic density [8–11] .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical nitrogen reduction reaction (NRR) powered by renewable energy sources is potentially a sustainable approach for nitrogen (N 2 ) fixation. However, the inert nature of N 2 and intensive competition from hydrogen evolution reaction (HER) impede its performance with sluggish kinetics and low selectivity [3–7] . Ru‐based transition metal catalysts are active catalysts for NRR at ambient conditions that can activate and polarize the inert N 2 molecule by accepting and donating electronic density [8–11] .…”
Section: Figurementioning
confidence: 99%
“…However, the inert nature of N 2 and intensive competition from hydrogen evolution reaction (HER) impede its performance with sluggish kinetics and low selectivity. [3][4][5][6][7] Ru-based transition metal catalysts are active catalysts for NRR at ambient conditions that can activate and polarize the inert N 2 molecule by accepting and donating electronic density. [8][9][10][11] However, they are limited by the low selectivity and faradaic efficiency (FE) towards NH 3 that could be attributed to the high affinity of H-adsorption on the Ru surface.…”
mentioning
confidence: 99%
“…The sluggish HER kinetics of the H-MoS 2 @NC in alkaline media results from its inability to effectively adsorb hydroxyl species on its surface, leading to being inefficient to discharge H 2 O, which is further proved by DFT calculation of the H 2 O dissociation energy barriers. [8,53,54] As shown in Figure S17, Supporting Information, the water dissociation energy barrier of Mo 25 S 50 is as high as 3.80 eV. After the substitution of S by P, the H 2 O dissociation barriers of Mo 25 S 49 P, and Mo 25 S 48 P 2 are reduced to 1.93 and 1.75 eV, respectively, indicating that a higher concentration of P in Mo 25 S 50 can decrease the H 2 O dissociation barriers, thus promoting H 2 O dissociation and accelerating the rate of H* formation.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6] Presently, considerable progress has been made in exploring non-noble metal electrocatalysts for water splitting, including transition metal oxides, chalcogenides, and phosphides, etc. [3,7,8] Among these developed catalytic materials, molybdenum (Mo)-based materials have attracted considerable interest for energy conversion. [9][10][11] For example, molybdenum phosphide (MoP) possesses high electronic conductivity (>5000 S cm −1 ) and electrochemical activity, which is beneficial for electrocatalytic applications such as hydrogenation and hydrodesulfurization.…”
Section: Introductionmentioning
confidence: 99%
“…Our group recently reported heterostructured Ni 2 P/NiTe 2 catalysts prepared via phosphine vapor-assisted approach for efficient HER, delivering 10 mA cm −2 at an overpotential of merely 62 mV. 70 The outstanding HER performance is originated from the abundant active sites and lower kinetic barrier for water dissociation on the interface of Ni 2 P/NiTe 2 electrocatalyst. Liang et al 19 reported the integration of NiFe oxyhydroxide with NiFe alloy nanowires through a magnetic-field-assisted chemical deposition approach resulted in a significantly improved OER performance.…”
Section: Heterostructurementioning
confidence: 99%